2022
DOI: 10.3390/ani12151927
|View full text |Cite
|
Sign up to set email alerts
|

The Replacement of Ground Corn with Sugar Beet in the Diet of Pasture-Fed Lactating Dairy Cows and Its Effect on Productive Performance and Rumen Metabolism

Abstract: (1) Background: Sugars have a potential to provide great amounts of fermentable energy in the rumen. Feeding fresh sugar beet (SB) to dairy cattle to replace a portion of the grain in the ration has not received sufficient attention. This study determined dry matter intake (DMI), feeding behavior, rumen fermentation and milk production responses when replacing corn grain with increasing levels of SB in pasture-fed lactating dairy cow diets. (2) Methods: A total of 12 early-lactation cows were used in a replica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 53 publications
0
3
0
1
Order By: Relevance
“…Then, lower DMI of pasture in the SBS treatment could be explained by the greater volume in the rumen of pieces of sugar beet silage used to ruminate in this group of cows; this gave a feeling of satiety in the cows because the rumen was filled; consequently, the cows’ desire to graze was reduced. Keim et al [ 25 ] observed a reduction in DMI with the inclusion of sugar beet in the diet, which was associated with a greater eating time due to the physical structure (difficult to eat) of sugar beet roots. Furthermore, it is known that there is variability with respect to the rate and degree of degradation and end products of carbohydrate fermentation [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, lower DMI of pasture in the SBS treatment could be explained by the greater volume in the rumen of pieces of sugar beet silage used to ruminate in this group of cows; this gave a feeling of satiety in the cows because the rumen was filled; consequently, the cows’ desire to graze was reduced. Keim et al [ 25 ] observed a reduction in DMI with the inclusion of sugar beet in the diet, which was associated with a greater eating time due to the physical structure (difficult to eat) of sugar beet roots. Furthermore, it is known that there is variability with respect to the rate and degree of degradation and end products of carbohydrate fermentation [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…An increased sucrose supply through supplementation with sugar beet has previously been shown to increase milk fat concentration [ 13 , 27 , 28 ]. Recently, Keim et al [ 25 ] observed an increase in milk fat content when sugar beet roots replaced corn in the diets of pasture-fed dairy cows. Schmidt et al [ 15 ] found a lower concentration of milk fat when molasses and barley were replaced with sugar beet silage.…”
Section: Discussionmentioning
confidence: 99%
“…Entre as diversas fontes de ingredientes energéticos, os grãos cereais são as principais fontes utilizadas, (Merino et al, 2021). Porém, estes insumos apresentam uma alta variação de preço no decorrer do ano por serem utilizados para diversas finalidades como na produção de alimentos e de biocombustíveis (Keim et al, 2022). Dessa forma, um dos maiores desafios nas propriedades leiteiras é avaliar os alimentos que podem ser utilizados de forma a obter lucratividade com a produção, apesar das variações nos custos de aquisição dos insumos (Heard et al, 2021).…”
Section: Introductionunclassified
“…Most studies evaluating the effects of supplemental sugars on ruminal digestion and fermentation involved isoprotein diets (~60:40 concentrate-to-forage ratio) offered to dairy cows [7,8], or the ruminal infusion of sugars to animals receiving the same forage-based diet [10,11]. On the other hand, replacing steam-flaked corn (SFC) with feed ingredients rich in sugars (i.e., sugar beets) increased the MP flow to the duodenum in feedlot cattle [12], and numerically increased (9.8%) the MP synthesis in lactating dairy cows [13]. Replacing corn with sugar beets did not greatly affect the diet composition (similar CP and NDF concentration between corn diets and sugar beet diets) [12].…”
Section: Introductionmentioning
confidence: 99%